Research on measurement method of drilling fluid rheological parameters based on helical pipe - Zhao, Jiahui; Hu, Zhongzhi; Zhu, Kuanliang; Zhou, Yan; Song, Wei (International Journal of Computer Science and Information Technology, 2023)
Monitoring drilling fluid rheological parameters can provide a basis for assessing downhole complexities and analyzing well control risks. Among various methods for measuring drilling fluid rheological parameters, the pipe flow method allows for real-time online measurements. However, it faces limitations due to the long length of pipes and challenges in miniaturization. Based on a survey of domestic and international research, this study conducted numerical simulations to analyze the differences in flow pressure drop of drilling fluid between helical pipes and straight pipes. It clarified the impact of helical pipe structural parameters, drilling fluid process parameters, and rheological parameters on drilling fluid flow pressure drop. Utilizing the constitutive equations of Bingham, power-law, and Herschel-Bulkley fluids, a regression model was established to convert the flow pressure drop of drilling fluid between helical pipes and straight pipes. The reliability of the numerical simulation results was verified using a self-developed drilling fluid flow pressure measurement device, which yielded an average relative error of only 2.13%. These research findings provide a theoretical basis for the development of drilling fluid rheological parameter monitoring devices based on helical pipes and the corresponding software.